Peran Pokdarwis Nyaru Menteng Dalam Meningkatkan Kesejahteraan Masyarakat Tumbang Tahai - Sri Rohaetin; Fendy Hariatama; Grace Evelina Buji; Dewi Rakhmawati; Liling Lenlioni (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
This research examines the important role of Pokdarwis Nyaru Menteng in improving community welfare in Tumbang Tahai sub-district of Palangka Raya city, focusing on ecotourism and its impact on community empowerment, environmental management, and local economic growth. Using a qualitative approach, the research involved direct observation and in-depth interviews with key stakeholders, including local residents, Pokdarwis leaders and administrators, and government agencies such as the forestry and tourism offices of central Kalimantan province and Palangka Raya city. The findings of this study highlight that Pokdarwis have successfully engaged local communities in tourism activities, leading to improved social and economic welfare. However, challenges related to managerial capacity and economic sustainability remain, particularly in relation to fluctuating visitor numbers. This research underscores the need for continued government support, enhanced managerial training and diversification strategies to ensure long-term economic stability. In addition, better environmental management practices are needed to preserve local biodiversity. This research contributes to a broader understanding of community-based tourism by emphasizing the importance of local participation and sustainable practices in tourism management to achieve improved welfare for the community